Applications and Immunological Effects of Quantum Dots on Respiratory System - Ren, Laibin; Wang, Lingwei; Rehberg, Markus; Stoeger, Tobias; Zhang, Jianglin; Chen, Shanze (Frontiers in Immunology, 2022)
Quantum dots (QDs), are one kind of nanoscale semiconductor crystals with specific electronic and optical properties, offering near-infrared mission and chemically active surfaces. Increasing interest for QDs exists in developing theranostics platforms for bioapplications such as imaging, drug delivery and therapy. Here we summarized QDs’ biomedical applications, toxicity, and immunological effects on the respiratory system. Bioapplications of QDs in lung include biomedical imaging, drug delivery, bio-sensing or diagnosis and therapy. Generically, toxic effects of nanoparticles are related to the generation of oxidative stresses with subsequent DNA damage and decreased lung cells viability in vitro and in vivo because of release of toxic metal ions or the features of QDs like its surface charge. Lastly, pulmonary immunological effects of QDs mainly include proinflammatory cytokines release and recruiting innate leukocytes or adaptive T cells.